Association of MTHFR rs1801133, PEMT rs4244593, CHKA rs7928739, VNTRs IL-1RN intron 2 and NOS3 intron 4 polymorphisms with unexplained intrauterine fetal death in Bangladeshi population - Mahasin, Deera; Bushra, Luthfa Akter; Nusrat, Shifat E (Brac University, 2024)
This thesis submitted to the Department of Mathematics and Natural Sciences in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology,2024.